Effects of tillage methods and water regimes on soil properties and yield of lowland rice from a sandy loam soil in southwest Nigeria - Ogunremi, L.T.; Lal, R.; Babalola, O. (1986)
Field experiments were conducted on a sandy loam soil (Aeric Tropaquent) during 1981 adn 1982 to assess the effects of compaction, puddling and no-till systems on soil physical properties and on rice growth and yield with and without supplementary irrigation. Soil compaction decreased macro- and micro-pores more than puddling or no-till treatments. The equilibrium infiltration rates were 0.12, 0.15 and 1.65 μm s−1 in compacted, ploughed and no-till treatments, respectively. The saturated hydraulic conductivity, void ratio and moisture content at −0.01 and −1.5 MPa water potential followed a similar trend. The mean weight diameters were 2.40, 2.36 and 2.09 mm for compacted, puddled and no-till treatments, respectively. The mean grain yields for 4 consecutive crops were 6.4, 5.1 and 4.9 Mg ha−1, the compacted being significantly greater than the puddled and no-till treatments. Compared with both puddling and no-till treatments, soil compaction resulted in significant yield increases of about 20% under the rain-fed regime and from 34 to 40% in the flooded moisture regime. There was about 26% increase in rice grain yield by continuous flooding over the rain-fed treatments, with the rice producing greater dry matter and biological yields due to a higher uptake of P, Ca, Mg, K, Na, Mn, Fe and Zn.